2019
DOI: 10.1038/s41598-019-54719-5
|View full text |Cite
|
Sign up to set email alerts
|

Effects of temperature and superparasitism on quality and characteristics of thelytokous Wolbachia-infected Trichogramma dendrolimi Matsumura (Hymenoptera: Trichogrammatidae) during mass rearing

Abstract: Thelytokous Wolbachia-infected Trichogramma spp. are widely used egg parasitoids against lepidopteran pests in biological control programs. Wolbachia may manipulate host wasps for superparasitism and is sensitive to temperature. To explore effects of temperature and superparasitism, we compared fitness parameters and Wolbachia-mediated phenotype of thelytokous Wolbachia-infected Trichogramma dendrolimi between those emerging from superparasitised or single-parasitised hosts at 17, 21, 25, or 29 °C. Infected mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
24
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 14 publications
(27 citation statements)
references
References 58 publications
3
24
0
Order By: Relevance
“…Therefore, it can be imagined that in the competition experiment, some of the W + offspring were produced by W – mothers and acquired Wolbachia while feeding with/on a W + larva within the same mealybug. Indeed, Wolbachia was recently shown to increase superparasitation behavior, while reducing the overall fitness of its parasitoid host in a mass‐rearing facility 77 . Interestingly, both W + and W – had much higher lifetime fecundity (54.5 and 63.2 offspring, respectively) than what has been previously reported (a maximum of less than 40; summarized in Suma et al 78 …”
Section: Discussionmentioning
confidence: 91%
“…Therefore, it can be imagined that in the competition experiment, some of the W + offspring were produced by W – mothers and acquired Wolbachia while feeding with/on a W + larva within the same mealybug. Indeed, Wolbachia was recently shown to increase superparasitation behavior, while reducing the overall fitness of its parasitoid host in a mass‐rearing facility 77 . Interestingly, both W + and W – had much higher lifetime fecundity (54.5 and 63.2 offspring, respectively) than what has been previously reported (a maximum of less than 40; summarized in Suma et al 78 …”
Section: Discussionmentioning
confidence: 91%
“…Nevertheless, our previous studies and others indicated that infected Trichogramma females show a higher probability of superparasitism, which parasitoid females lay a second clutch of eggs on a host that has been parasitised by the same species (Harvey et al, 2013;Farahani et al, 2015;Huang et al, 2017a;Liu et al, 2018;Zhou et al, 2019b). According to Lack's hypothesis as applied to gregarious parasitoids by Lack (1947) and Charnov and Skinner (1984), parasitoid females always allocate an optimal clutch size to a host to maximize offspring fitness.…”
Section: Introductionmentioning
confidence: 93%
“…Considering these two opposite hypotheses, an important question that should be tested arises: is the effect of Wolbachia on the fitness of Trichogramma offspring positive or negative in superparasitised hosts? Although previous studies have shown that Trichogramma infected by Wolbachia have higher probability for superparasitism (Huigens et al, 2004b;Farahani et al, 2015;Zhou et al, 2019bZhou et al, , 2020, the fate of Trichogramma offspring in the superparasitised host is still unknown.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Intraspeci c competition may occur when the female wasp deposits a second clutch of eggs on a host that has been parasitized by the same parasitoid species. This is termed "superparasitism" (Van Alphen and Visser 1990; Zhou et al 2019b).…”
Section: Introductionmentioning
confidence: 99%